Understanding complexity by clustering data with maching learning and R - Lantz, Brett (O'Reilly Media, 2014)
"Although machine learning is most commonly used for prediction, it can also help make sense of the complexity in the world around us. In this webcast, we explore how R's open-source clustering packages can discover patterns in large data and inform our understanding of complex sociological phenomena such as teenage identities."--Resource description page.